Peptide Regulation of Gene Expression: A Systematic Review - Vladimir Khatskelevich Khavinson (MDPI AG, 2021)
Peptides are characterized by their wide range of biological activity: they regulate functions of the endocrine, nervous, and immune systems. The mechanism of such action of peptides involves their ability to regulate gene expression and protein synthesis in plants, microorganisms, insects, birds, rodents, primates, and humans. Short peptides, consisting of 2–7 amino acid residues, can penetrate into the nuclei and nucleoli of cells and interact with the nucleosome, the histone proteins, and both single- and double-stranded DNA. DNA–peptide interactions, including sequence recognition in gene promoters, are important for template-directed synthetic reactions, replication, transcription, and reparation. Peptides can regulate the status of DNA methylation, which is an epigenetic mechanism for the activation or repression of genes in both the normal condition, as well as in cases of pathology and senescence. In this context, one can assume that short peptides were evolutionarily among the first signaling molecules that regulated the reactions of template-directed syntheses. This situation enhances the prospects of developing effective and safe immunoregulatory, neuroprotective, antimicrobial, antiviral, and other drugs based on short peptides.